Pengaruh Belanja Jasa Profesi dan Transpor Layanan Pernikahan di Luar Kantor terhadap Beban Kinerja dan Anggaran Ditjen Bimas Islam Tahun 2019-2022 - Aji, Hastomo (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2023)
This policy paper describes the influence of expenditure on professional services and transportation of celebrants at the District KUA, especially in out-of-office wedding services, on the performance and budget burden on the Directorate General of Islamic Community Guidance. This step is an effort to mitigate and resolve budgeting problems through the reconstruction of PNBP-NR management. However, in its implementation, it turned out to conflict with several related policies. In studying this problem, the author uses a qualitative method as an interpretive method, because the research data is more concerned with the interpretation of data found in the field. In general, the data in this study shows that the initial aim of implementing the allocation of costs for professional services and transportation for marriage service officers outside the office was to minimize illegal fees and gratuities. This policy was implemented because the budget posture at the Directorate General of Islamic Community Guidance was unbalanced, where budget logistics from Pure Rupiah funding sources were mostly used for routine office operational expenditure, while the majority of non-operational activity allowances were charged to PNBP-NR funding sources, whose budget revenues based on the number of wedding events held outside the office, so the planned work program will not be able to run if the source of PNBP-NR revenue is not reached according to the target.